The Allocation of Public School Expenditures - Kelly Bedard; William O. Brown Jr. (Claremont McKenna College, Department of Economics, 2000)
While the Serrano v Priest decisions and Proposition 13 effectively rendered California school district budgets exogenous, intra-district resource allocation remains largely at the discretion of school district administrations. As a result, Serrano v Priest and Proposition 13 alleviate concerns about the potentially endogenous relationship between student body composition and inter-district resource disparity and allow us to focus on consistently estimating the effect of classroom versus non-classroom spending. We find that teaching expenditures have a positive effect on student performance while nonteaching expenditures have a negative effect. Either the reallocation of 100 from administrative to classroom spending, with no change in overall expenditures, or an 100 increase aimed directly at the classroom moves the average California high school approximately 5 percentage points higher in the state test score rankings. These results are similar across grade levels (elementary, middle and high schools) and subject areas (mathematics, reading, language, spelling, social studies, and science). Our results suggest that both current and future educational expenditures should be targeted towards the classroom.
Keywords: H52; L2; 330; school spending; test scores